Emergence of a distinct HIV-specific IL-10-producing CD8+ T-cell subset with immunomodulatory functions during chronic HIV-1 infection. - Clutton, G; Yang, H; Hancock, G; Sande, N; Holloway, C; Angus, B; von Delft, A; Barnes, E; Borrow, P; Pellegrino, P; Williams, I; McMichael, A; et al. (2013)
Interleukin-10 (IL-10) plays a key role in regulating proinflammatory immune responses to infection but can interfere with pathogen clearance. Although IL-10 is upregulated throughout HIV-1 infection in multiple cell subsets, whether this is a viral immune evasion strategy or an appropriate response to immune activation is unresolved. Analysis of IL-10 production at the single cell level in 51 chronically infected subjects (31 antiretroviral (ART) naïve and 20 ART treated) showed that a subset of CD8(+) T cells with a CD25(neg) FoxP3(neg) phenotype contributes substantially to IL-10 production in response to HIV-1 gag stimulation. The frequencies of gag-specific IL-10- and IFN-γ-producing T cells in ART-naïve subjects were strongly correlated and the majority of these IL-10(+) CD8(+) T cells co-produced IFN-γ; however, patients with a predominant IL-10(+) /IFN-γ(neg) profile showed better control of viraemia. Depletion of HIV-specific CD8(+) IL-10(+) cells from PBMCs led to upregulation of CD38 on CD14(+) monocytes together with increased IL-6 production, in response to gag stimulation. Increased CD38 expression was positively correlated with the frequency of the IL-10(+) population and was also induced by exposure of monocytes to HIV-1 in vitro. Production of IL-10 by HIV-specific CD8(+) T cells may represent an adaptive regulatory response to monocyte activation during chronic infection.